Lithium composite oxide for lithium secondary battery and method for producing same
By forming lithium composite oxide secondary particles with a decreasing interfacial distance from the center to the surface and applying a Co coating layer, the issues of residual lithium in lithium secondary batteries are addressed, resulting in enhanced capacity, resistance, and lifetime characteristics.
Patent Information
- Application Number
- JP2022154709
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2016-10-10
- Filing Date
- 2022-09-28
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2037-03-30
AI Technical Summary
Lithium secondary batteries face issues with high residual lithium levels, leading to deterioration in high temperature safety, capacity, efficiency, and lifetime characteristics due to unreacted lithium compounds reacting with electrolytes and causing gas generation and swelling.
The development of lithium composite oxide secondary particles with a unique structure, where the interfacial distance of the crystal structure decreases from the center to the surface, combined with a Co coating layer on the surface, effectively reduces residual lithium and enhances capacitance, resistance, and lifetime characteristics.
This approach significantly reduces residual lithium, thereby improving the capacity, resistance, and lifetime characteristics of lithium secondary batteries, while maintaining high temperature safety and efficiency.
Smart Images

Figure 0007649770000012 
Figure 0007649770000013 
Figure 0007649770000014
Abstract
Description
[Technical field]
[0001] The present invention relates to a lithium composite oxide and a manufacturing method thereof, and more particularly, to a cathode active material in which lithium ion diffusion pathways are formed in the a-axis and c-axis directions of a conventional crystal structure, in which water washing is performed in the manufacturing process to improve residual lithium. As a result of the water washing, the residual lithium is reduced, but as a deterioration in performance is induced, a coating of a different element is carried out on the surface, and as the interplanar distance of the crystal structure between the primary particles located inside the secondary particles and the primary particles located on the surface of the secondary particles changes, the lithium composite oxide and its manufacturing method show an effect of improving capacity characteristics, resistance characteristics, and life characteristics. [Background technology]
[0002] As technology and demand for mobile devices increases, the demand for secondary batteries as an energy source is growing rapidly. Among such secondary batteries, lithium secondary batteries, which exhibit high energy density and working potential, long cycle life, and low self-discharge rate, have been commercialized and are widely used. The positive electrode active material for lithium secondary batteries is lithium-containing cobalt oxide (LiCoO 2 ) is mainly used, and LiMnO 2 , LiMn with spinel crystal structure 2 O 4 Lithium-containing manganese oxides such as LiNiO 2 The use of is also being considered. Among the positive electrode active materials, LiCoO 2 is the most widely used due to its excellent life characteristics and charge / discharge efficiency, but it has a drawback in that it has a small capacity and is expensive due to the limited availability of cobalt as a raw material, so it has a limited price competitiveness when used in large quantities as a power source for medium and large batteries such as electric vehicles. 2 , LiMn 2 O 4Lithium manganese oxides such as those described above have the advantages of being inexpensive, environmentally friendly, and excellent thermal safety because manganese resources used as a raw material are abundant. However, they have problems such as small capacity and poor high-temperature characteristics and cycle characteristics.
[0003] A method for preparing a lithium composite oxide generally includes the steps of preparing a transition metal precursor, mixing the transition metal precursor with a lithium compound, and then calcining the mixture. In this case, the lithium compound includes LiOH and / or Li 2 CO 3 Generally, when the Ni content of the positive electrode active material is 65% or less, Li 2 CO 3 When the Ni content is 65% or more, it is preferable to use LiOH since it is a low temperature reaction. However, nickel-rich systems with Ni content of 65% or more are low-temperature reactions, so LiOH and Li 2 CO 3 However, there is a problem in that the amount of residual lithium present in the form of unreacted LiOH and Li 2 CO 3 When LiOH reacts with electrolyte in the battery, it generates gas and causes swelling, which seriously reduces safety at high temperatures. In addition, unreacted LiOH has high viscosity during slurry mixing before manufacturing electrodes, which can cause gelation.
[0004] In order to remove such unreacted Li, a water washing process is generally carried out after the preparation of the active material, and the amount of residual lithium is significantly reduced. However, in this case, the surface of the positive electrode active material is damaged in the water washing process, resulting in a decrease in capacity and efficiency characteristics, and further problems such as an increase in resistance during high-temperature storage are caused. Thus, a method for reducing the residual lithium and improving capacity, efficiency, and life characteristics is required. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Republic of Korea Patent Publication No. 10-2011-0108566 Summary of the Invention [Problem to be solved by the invention]
[0006] In order to solve the above problems, the present invention aims to provide a lithium composite oxide having a new structure that reduces residual lithium and improves capacity characteristics, resistance characteristics, and life characteristics. [Means for solving the problem]
[0007] In order to solve the above-mentioned problems, the present invention provides lithium composite oxide secondary particles formed by agglomeration of a plurality of primary particles, characterized in that the interplanar distance of the crystal structure of the primary particles decreases from the center of the secondary particles toward the surface. In the lithium composite oxide secondary particles according to the present invention, the interplanar distances d1 and d2 refer to the average of 10 adjacent interplanar distances centered on the interplanar distance of a portion measured from the results of a crystal structure analysis such as a TEM analysis of the positive electrode active material. The decrease in the interplanar distance from the center to the surface of the secondary particles includes both the decrease in the interplanar distance from the center to the surface in the primary particles and the decrease in the interplanar distance in the primary particles located at the surface compared to the interplanar distance in the primary particles located at the center of the secondary particles.
[0008] In the secondary particles of the lithium composite oxide according to the present invention, the interplanar distance d1 of the crystal structure inside the secondary particles is 4.8 nm or more. In the secondary particles of the lithium composite oxide according to the present invention, the interplanar distance d2 of the crystal structure on the surface of the secondary particles is 4.75 nm or less. In the lithium composite oxide secondary particles according to the present invention, the lithium composite oxide secondary particles have a hexagonal structure, and are characterized in that a lithium ion diffusion path is formed from the surface of the particle toward the center. In the lithium composite oxide secondary particles according to the present invention, the secondary particles include a Co coating layer on the surface thereof, and the thickness of the surface is 0.3 to 1 um. That is, in the lithium composite oxide secondary particles according to the present invention, the primary particles located on the surface are primary particles located within a thickness of 0.3 to 1 um at the outermost periphery of the secondary particles.
[0009] The secondary lithium composite oxide particles according to the present invention are characterized in that at least one peak appears at the positions of (104), (110), (113), (101), (102), and (003) during XDR analysis. The peaks appearing at the positions of (104), (110), (113), (101), (102), and (003) are characteristic peaks appearing in LiCoO2 particles, and the secondary lithium composite oxide particles according to the present invention exhibit such characteristic peaks due to the Co coating after the water washing process. The secondary lithium composite oxide particles according to the present invention are characterized in that the binding energy (P1) of the spin-orbit-spit 2p3 / 2 peak and the binding energy (P2) of the 2p1 / 2 peak in the Co 2p core-level spectrum analysis obtained through XPS measurement are as follows. 779 eV ≦ (P1) ≦ 780 eV 794 eV ≦ (P2) ≦ 795 eV
[0010] The lithium composite oxide secondary particles according to the present invention are characterized in that the ratio of the peak intensity (I531) around 531 eV and the peak intensity (I528) around 528.5 eV in the O 1s core-level spectrum analysis obtained through XPS measurement is as follows. (I531) / (I528)<2
[0011] The secondary particles of lithium composite oxide according to the present invention are characterized in that the ratio of the peak intensity (I289) around 289 eV and the peak intensity (I284) around 284.5 eV in the C 1s core-level spectrum analysis obtained through XPS measurement is as follows. (I289) / (I284)<0.9
[0012] The lithium composite oxide secondary particles according to the present invention are characterized by being represented by the following <Chemical Formula 1>. [ka] (In the <Chemical Formula 1>, M1 is Mn or Al, M2 and M3 are metals selected from the group consisting of Al, Ba, B, Co, Ce, Cr, F, Li, Mg, Mn, Mo, P, Sr, Ti, and Zr, and 0.95≦X1≦1.05, 1.50≦a≦2.1, 0.02≦x1≦0.25, 0.01≦y1≦0.20, 0≦z1≦0.20, and 0≦r1≦0.20)
[0013] The present invention also provides The first step is to manufacture a positive electrode active material precursor for a lithium secondary battery represented by the following <Chemical Formula 2>. UP; [ka] (In the <Chemical Formula 2>, M1 is Mn or Al, and M2 is a metal selected from the group consisting of Al, Ba, B, Co, Ce, Cr, F, Li, Mg, Mn, Mo, P, Sr, Ti, and Zr, (0≦x2≦0.25, 0≦y2≦0.20, 0≦z2≦0.20)
[0014] a second step of reacting the positive electrode active material precursor for a lithium secondary battery with a lithium compound and subjecting the resulting mixture to a first heat treatment to prepare a positive electrode active material; a third step of washing the positive electrode active material with distilled water or an alkaline aqueous solution; a fourth step of coating the washed positive electrode active material with a solution containing a metal M2 selected from the group consisting of Al, Ba, B, Co, Ce, Cr, F, Li, Mg, Mn, Mo, P, Sr, Ti, and Zr; a fifth step of drying the positive electrode active material particles; and a sixth step of mixing the dried positive electrode active material with a metal M3 selected from the group consisting of Al, Ba, B, Co, Ce, Cr, F, Li, Mg, Mn, Mo, P, Sr, Ti, and Zr, and performing a second heat treatment to dope the metal M3 into the inside of the particles.
[0015] In the method for producing a positive electrode active material according to the present invention, the fourth step is characterized in that a coating reaction is carried out with a Co-containing solution. The present invention also provides a lithium secondary battery comprising the lithium composite oxide secondary particles according to the present invention. The lithium secondary battery according to the present invention is characterized in that the residual lithium is 6000 ppm or less. Effect of the Invention
[0016] In the lithium composite oxide of the present invention, the interplanar distance of the crystal structure is different between the inside and the surface of the secondary particles due to the water washing process and the heterogeneous metal coating process, and therefore, a secondary battery including the lithium composite oxide of the present invention exhibits the effects of reducing residual lithium and improving capacity characteristics, resistance characteristics, and life characteristics. [Brief description of the drawings]
[0017] [Figure 1] 1 shows the results of measuring the diffraction pattern and interplanar distance of the LiCoO2 positive electrode active material of Comparative Example 1 of the present invention. [Diagram 2] 4 shows the results of measuring a TEM photograph and an EDX photograph of a positive electrode active material prepared in one embodiment of the present invention. [Diagram 3] 4 shows the results of measuring the diffraction pattern and interplanar distance of a positive electrode active material prepared in one embodiment of the present invention. [Figure 4]4 shows the results of measuring a TEM photograph and an EDX photograph of a positive electrode active material prepared in one embodiment of the present invention. [Diagram 5] 4 shows the results of measuring the diffraction pattern and interplanar distance of a positive electrode active material prepared in one embodiment of the present invention. [Figure 6] 1 shows the results of measuring the change in concentration of Ni, Co, and Al from the surface portion toward the center portion of a positive electrode active material prepared in an embodiment of the present invention. [Figure 7] 1 shows the results of measuring an EDX photograph of a positive electrode active material prepared in one embodiment of the present invention. [Figure 8] 4 shows the results of measuring the diffraction pattern and interplanar distance of a positive electrode active material prepared in one embodiment of the present invention. [Figure 9] 4 shows the results of measuring a TEM photograph and an EDX photograph of a positive electrode active material prepared in one embodiment of the present invention. [Figure 10] 1 shows the results of measuring the change in concentration of Ni, Co, and Al from the surface portion toward the center portion of a positive electrode active material prepared in an embodiment of the present invention. [Figure 11] 1 shows the results of measuring the change in concentration of Ni, Co, and Al toward the center at three points on the surface of a positive active material prepared in an embodiment of the present invention. [Figure 12] 4 shows the results of measuring the diffraction patterns and interplanar distances of the positive electrode active materials prepared in an example of the present invention and a comparative example. [Figure 13] 4 shows the results of measuring the diffraction patterns and interplanar distances of the positive electrode active materials prepared in an example of the present invention and a comparative example. [Figure 14] 4 shows the results of measuring the diffraction patterns and interplanar distances of the positive electrode active materials prepared in an example of the present invention and a comparative example. [Figure 15] 1 shows the results of measuring an EDX photograph of an active material produced in a comparative example of the present invention. [Figure 16] 1 shows the results of measuring an EDX photograph of an active material produced in a comparative example of the present invention. [Figure 17] 4 shows the results of measuring the diffraction patterns and interplanar distances of the positive electrode active materials prepared in an example of the present invention and a comparative example. [Figure 18] 4 shows the results of measuring the diffraction patterns and interplanar distances of the positive electrode active materials prepared in an example of the present invention and a comparative example. [Figure 19] 4 shows the results of measuring the diffraction patterns and interplanar distances of the positive electrode active materials prepared in an example of the present invention and a comparative example. [Figure 20] 1 shows the results of measuring the change in concentration of Ni, Co, and Al from the surface portion toward the center portion of a positive electrode active material prepared in an embodiment of the present invention. [Figure 21] 1 shows the results of measuring the change in concentration of Ni, Co, and Al from the surface portion toward the center portion of a positive electrode active material prepared in an embodiment of the present invention. [Figure 22] 1 shows the results of measuring XRD of positive electrode active materials prepared in an example and a comparative example of the present invention. [Figure 23] 1 shows the results of measuring XRD of positive electrode active materials prepared in an example and a comparative example of the present invention. [Figure 24] 1 shows the results of measuring XRD of positive electrode active materials prepared in an example and a comparative example of the present invention. [Diagram 25] 1 shows the results of measuring XRD of positive electrode active materials prepared in an example and a comparative example of the present invention. [Figure 26] 1 shows the results of XPS measurement of positive electrode active materials prepared in an example and a comparative example of the present invention. [Figure 27a] 1 shows the results of measuring the characteristics of batteries including the positive electrode active materials prepared in an example and a comparative example. [Figure 27b] 1 shows the results of measuring the characteristics of batteries including the positive electrode active materials prepared in an example and a comparative example. [Figure 27c] 1 shows the results of measuring the characteristics of batteries including the positive electrode active materials prepared in an example and a comparative example. [Fig. 27d] 1 shows the results of measuring the characteristics of batteries including the positive electrode active materials prepared in an example and a comparative example. [Figure 27e] 1 shows the results of measuring the characteristics of batteries including the positive electrode active materials prepared in an example and a comparative example. [Figure 28a]1 shows the results of measuring the characteristics of batteries including the positive electrode active materials prepared in an example and a comparative example. [Figure 28b] 1 shows the results of measuring the characteristics of batteries including the positive electrode active materials prepared in an example and a comparative example. [Figure 28c] 1 shows the results of measuring the characteristics of batteries including the positive electrode active materials prepared in an example and a comparative example. [Fig. 28d] 1 shows the results of measuring the characteristics of batteries including the positive electrode active materials prepared in an example and a comparative example. [Figure 28e] 1 shows the results of measuring the characteristics of batteries including the positive electrode active materials prepared in an example and a comparative example. [Figure 29a] 1 shows the results of measuring the characteristics of batteries including the positive electrode active materials prepared in an example and a comparative example. [Figure 29b] 1 shows the results of measuring the characteristics of batteries including the positive electrode active materials prepared in an example and a comparative example. [Figure 29c] 1 shows the results of measuring the characteristics of batteries including the positive electrode active materials prepared in an example and a comparative example. [Figure 29d] 1 shows the results of measuring the characteristics of batteries including the positive electrode active materials prepared in an example and a comparative example. [Figure 29e] 1 shows the results of measuring the characteristics of batteries including the positive electrode active materials prepared in an example and a comparative example. [Figure 30a] 1 shows the results of measuring the characteristics of batteries including the positive electrode active materials prepared in an example and a comparative example. [Figure 30b] 1 shows the results of measuring the characteristics of batteries including the positive electrode active materials prepared in an example and a comparative example. [Figure 30c] 1 shows the results of measuring the characteristics of batteries including the positive electrode active materials prepared in an example and a comparative example. [Figure 30d] 1 shows the results of measuring the characteristics of batteries including the positive electrode active materials prepared in an example and a comparative example. [Figure 30e]1 shows the results of measuring the characteristics of batteries including the positive electrode active materials prepared in an example and a comparative example. [Figure 31a] 1 shows the results of measuring the characteristics of batteries including the positive electrode active materials prepared in an example and a comparative example. [Figure 31b] 1 shows the results of measuring the characteristics of batteries including the positive electrode active materials prepared in an example and a comparative example. [Fig. 31c] 1 shows the results of measuring the characteristics of batteries including the positive electrode active materials prepared in an example and a comparative example. [Fig. 31d] 1 shows the results of measuring the characteristics of batteries including the positive electrode active materials prepared in an example and a comparative example. [Figure 31e] 1 shows the results of measuring the characteristics of batteries including the positive electrode active materials prepared in an example and a comparative example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples. <Comparative Example 1> In Comparative Example 1, commercially available LiCoO 2 The positive electrode active material was used.
[0019] <Experimental Example> Measurement of distance between crystal structures The LiCoO 2 FIG. 1 shows the results of measuring the diffraction patterns and interplanar distances of primary particles located on the surface of a secondary particle of a positive electrode active material and primary particles located inside the particle. LiCoO 2 The positive electrode active material particles were placed on a carbon grid, carbon-coated, PT-coated, and sliced with an ion beam in a TEM pretreatment process. The image was magnified 20 to 25 million times, and the inter-plane distance of the part to be measured was measured as the average distance of 10 inter-plane distances on the left and right of the inter-plane distance to be measured. As shown in Figure 1, LiCoO 2The diffraction patterns of the primary particles located inside and on the surface of the secondary particles of the positive electrode active material all had a hexagonal structure, and the interplanar distances of the primary particles located inside and on the surface of the secondary particles were all measured to be 4.70 nm.
[0020] <Example 1> Preparation of positive electrode active material First, NiCo(OH) was prepared by coprecipitation. 2 The precursor was prepared. The lithium compound in the prepared precursor was Li 2 CO 3 and LiOH were added, and Al and Mg were added as M1, and a first heat treatment was performed to produce a positive electrode active material for a lithium secondary battery. Distilled water was prepared, and the positive active material for a lithium secondary battery was put into the distilled water, and the positive active material for a lithium secondary battery was washed with water while maintaining the temperature. Thereafter, 0.03 mol of cobalt sulfate solution was added to the positive active material washing solution at a constant rate for 1 hour while stirring the positive active material, and the surface of the positive active material was coated with Co in M2, washed with water, and dried at 120° C. under vacuum conditions. The coated positive electrode active material was added with Ti as M3, and subjected to a second heat treatment at 450° C. to produce a positive electrode active material for a lithium secondary battery.
[0021] <Experimental example> TEM, EDX measurement TEM and EDX images of the positive active material prepared in Example 1 were taken, and the results are shown in FIG. As shown in FIG. 2, in the case of the cathode active material prepared in Example 1 of the present invention, the Co concentration is high on the surface of the secondary particles and decreases from the surface to the inside of the secondary particles, indicating that the Co concentration is not constant within the secondary particles but shows a gradient.
[0022] <Experimental Example> Measurement of distance between crystal structures The diffraction patterns and interplanar distances of the primary particles located inside the secondary particles of the cathode active material prepared in Example 1 and the primary particles located on the surface coated with Co and Ti were measured, and the results are shown in FIG. 3. As shown in FIG. 3, the thickness of the Co coating layer is about 80 nm, and the diffraction pattern of the primary particles located inside the secondary particles has a hexagonal structure. In the case of the primary particles located inside the secondary particles, the average interplanar distance of 10 adjacent planes in the TEM photograph was measured to be 4.88 nm, whereas in the case of the primary particles located on the surface where the Co coating layer is present, the diffraction pattern has a hexagonal structure but the interplanar distance was measured to be 4.73 nm. As a result, the interplanar distance of the primary particles located on the surface is reduced compared to the primary particles located inside the secondary particles that are not coated with cobalt, and the interplanar distance of the primary particles located on the surface is smaller than that of the LiCoO 2 It can be seen that the interfacial distance has been changed to be similar to that of the
[0023] <Example 2> Preparation of positive electrode active material A positive active material of Example 2 was prepared by carrying out the same washing and coating processes as in Example 1, except that the concentration of the cobalt aqueous solution added to the positive active material washing solution was 4 mol %.
[0024] <Experimental example> TEM, EDX measurement TEM and EDX images of the positive active material prepared in Example 2 were taken, and the results are shown in FIG. As shown in FIG. 4, in the case of the cathode active material prepared in Example 2 of the present invention, the Co concentration is high on the surface of the secondary particles and decreases toward the inside of the secondary particles, so that the Co concentration within the particles is not constant but shows a gradient.
[0025] <Experimental Example> Measurement of distance between crystal structures The primary particles and Co, Ti, which are located inside the secondary particles of the positive active material prepared in Example 1 The diffraction patterns and interplanar distances of the primary particles located on the surface coated with ZnO were measured, and the results are shown in FIG. In FIG. 5, the thickness of the surface Co coating layer is about 90 nm, the diffraction pattern of the primary particles located inside the secondary particles is a hexagonal structure, and in the case of the primary particles located inside the secondary particles, the average interplanar distance of 10 adjacent planes in the TEM photograph is measured to be 4.85 nm, whereas in the case of the primary particles located on the surface where the Co coating layer exists, the diffraction pattern is a hexagonal structure but the interplanar distance is measured to be 4.73 nm. The interplanar distance of the primary particles located on the surface is reduced compared to the primary particles located inside the secondary particles that are not coated with cobalt, and the interplanar distance of the primary particles located on the surface is smaller than that of the LiCoO 2 It can be seen that the interfacial distance has been changed to be similar to that of the
[0026] <Example 3> Preparation of NCM-based positive electrode active material The same procedure as in Example 1 was carried out, and the positive active material of Example 3 was prepared by coating the positive active material with the cobalt aqueous solution added to the positive active material washing solution at a concentration of 5 mol %.
[0027] <Experimental Example> Concentration scanning The changes in the concentrations of Ni, Co, and Al from the surface of the secondary particles of the positive active material prepared in Example 3 toward the center of the particles were measured, and the results are shown in FIG. In FIG. 6, in the case of the positive active material prepared in Example 3 of the present invention, the Co coating layer in which Co is coated has a higher Co concentration from the surface toward the center, and then the Co concentration decreases toward the center, and the thickness of the Co coating layer is 0.1 um.
[0028] <Experimental example>TEM, EDX EDX images of Ni, Co, and Al were taken from the surface of the secondary particles of the positive active material prepared in Example 3 toward the center of the particles, and the results are shown in FIG. As shown in FIG. 7, in the case of the positive electrode active material prepared in Example 3, the Co concentration increases from the surface toward the center in the Co-coated layer, and then decreases toward the center, with the Co concentration being high along the boundaries of the primary particles.
[0029] <Experimental Example> Measurement of distance between crystal structures The diffraction patterns and interplanar distances of the primary particles located inside the secondary particles of the positive active material prepared in Example 3 and the primary particles located on the surface coated with Co and Ti were measured, and the results are shown in FIG. 8. As shown in FIG. 8, the thickness of the Co coating layer is about 100 nm, the diffraction pattern of the primary particles located inside the secondary particles is a hexagonal structure, and in the case of the primary particles located inside the secondary particles, the average interplanar distance of 10 adjacent planes in the TEM photograph is measured to be 4.84 nm, whereas in the case of the primary particles located on the surface where the Co coating layer is present, the diffraction pattern is a hexagonal structure but the interplanar distance is measured to be 4.67 nm. The interplanar distance of the primary particles located on the surface coated with Co is smaller than that of the primary particles located inside the secondary particles not coated with Co, and the interplanar distance of the primary particles located on the surface is smaller than that of the LiCoO 2 It can be seen that the interfacial distance has been changed to be similar to that of the
[0030] <Example 4> Preparation of NCM-based positive electrode active material The same procedure as in Example 1 was carried out, except that the concentration of the cobalt aqueous solution added to the washing solution for the positive active material was 10 mol %, and washing and coating were performed to prepare a positive active material of Example 4.
[0031] <Experimental example> TEM, EDX measurement TEM and EDX images were taken of the surface of the secondary particles of the positive active material prepared in Example 4, and the results are shown in FIG. As shown in FIG. 9, in the case of the cathode active material prepared in Example 4 of the present invention, the Co concentration is high on the surface of the secondary particles and decreases toward the inside of the secondary particles, so that the Co concentration is not constant but shows a gradient. In addition, the EDX measurement results show that Co is distributed in rod-shaped primary particles, and the Co concentration is measured to be high around the rod-shaped primary particles.
[0032] <Experimental Example> Concentration scanning inside particles The changes in the concentrations of Ni, Co, and Al from the surface to the center of the secondary particles of the positive active material prepared in Example 4 were measured, and the results are shown in FIG. As shown in FIG. 10, in the case of the cathode active material prepared in Example 4 of the present invention, the Co concentration increases from the surface toward the center in the coating layer portion where the secondary particles are coated with Co, and then the Co concentration decreases toward the center, and the thickness of the Co coating layer where Co is coated is 0.14 μm.
[0033] <Experimental Example> Concentration scanning The changes in the concentrations of Ni, Co, and Al were measured at three points on the surface of the secondary particles of the positive active material prepared in Example 4 from the surface to the center of the particle, and the results are shown in FIG. As shown in FIG. 11, a concentration gradient layer was uniformly formed in three independent portions of the surface of the secondary particle of the positive active material prepared in Example 4 with a coating layer thickness of 0.14 um.
[0034] <Experimental Example> Measurement of distance between crystal structures The diffraction patterns and interplanar distances of the primary particles located inside the secondary particles of the positive active material prepared in Example 4 and the primary particles located on the surface coated with Co and Ti were measured, and the results are shown in FIG. 12. As shown in FIG. 12, the thickness of the Co coating layer was 140 nm, and the diffraction pattern of the primary particles located inside the secondary particles was a hexagonal structure with an interplanar distance measured at 4.85 nm, whereas the diffraction pattern of the primary particles located on the surface coated with Co and Ti was a hexagonal structure with an interplanar distance measured at 4.69 nm. The interplanar distance of the primary particles located on the surface coated with Co is smaller than that of the primary particles located inside the secondary particles not coated with Co, and the interplanar distance of the primary particles located on the surface is smaller than that of the LiCoO 2 It can be seen that the interfacial distance has been changed to be similar to that of the
[0035] <Experimental Example> Measurement of distance between crystal structures on coating boundary surface FIG. 13 shows the results of measuring the diffraction pattern and interplanar distance at the inside of the primary particle located on the surface of the secondary particle of the positive active material prepared in Example 4 and at the boundary surface of the coating layer within the primary particle located on the surface of the secondary particle. As shown in FIG. 13, the diffraction pattern at the boundary between the primary particles located on the surface of the secondary particles of the positive electrode active material and the coating layer coated with Co and Ti in the primary particles located on the surface of the secondary particles had a hexagonal structure, and the interplanar distance was measured to be 4.71 nm. In the case of the primary particles located inside the secondary particles, the inter-plane distance was measured to be 4.85 nm, and in the case of the primary particles located on the surfaces of the secondary particles coated with cobalt and Ti, the inter-plane distance was measured to be 4.69 nm. In comparison, it can be seen that the inter-plane distance of 4.71 nm at the coating boundary surface within the primary particles located on the surfaces of the secondary particles coated with cobalt and Ti is measured to be the median value between the inter-plane distance of the primary particles located inside the secondary particles and the inter-plane distance of the primary particles located on the surfaces of the secondary particles coated with cobalt and Ti. In addition, the interfacial distance at the coating boundary surface is 2 It is similar to the distance between the faces of It can be seen that the following changes have been made:
[0036] <Experimental Example> Measurement of distance between crystal structures on the boundary surface of primary particles FIG. 14 shows the results of measuring the diffraction pattern and interplanar distance at the boundary between the primary particles and the surfaces of the secondary particles coated with Co and Ti of the positive active material prepared in Example 4. As shown in FIG. 14, the diffraction pattern of the primary particles at the boundary between the primary particles located at the surface of the secondary particle of the positive electrode active material has a hexagonal structure, and the interplanar distances are measured to be 4.69 and 4.71 nm, which are intermediate values between the interplanar distances of the core portion and the coating layer portion. In addition, the interplanar distance at the boundary of the primary particles is 2 It can be seen that the interfacial distance has been changed to be similar to that of the
[0037] <Example 5> Preparation of positive electrode active material The same procedure as in Example 1 was carried out, and the composition of the positive electrode active material for a lithium secondary battery that was subjected to the first heat treatment was Li 1.02 Ni 0.816 Co 0.15 Al 0.034 O 2 The positive electrode active material of Example 5 was produced without adding Ti.
[0038] <Example 6> Preparation of positive electrode active material The same procedure as in Example 1 was carried out, and the composition of the positive electrode active material for a lithium secondary battery that was subjected to the first heat treatment was Li 1.02 Ni 0.903 Co 0.08 Al 0.014 Mg 0.003 O 2 Thus, a positive electrode active material of Example 6 was produced.
[0039] <Example 7> Preparation of positive electrode active material The same procedure as in Example 1 was carried out, and the composition of the positive electrode active material for a lithium secondary battery that was subjected to the first heat treatment was Li 1.00 Ni 0.965 Co 0.02 Al 0.014 Mg 0.001 O 2 Thus, a positive electrode active material of Example 7 was produced.
[0040] <Example 8> Preparation of positive electrode active material The same procedure as in Example 7 was carried out, except that the concentration of the cobalt aqueous solution added to the washing solution for the positive active material was 4 mol %, to prepare a positive active material of Example 8.
[0041] <Example 9> Preparation of positive electrode active material The same procedure as in Example 7 was carried out, except that the concentration of the cobalt aqueous solution added to the washing solution for the positive active material was 5 mol %, to prepare a positive active material of Example 9.
[0042] <Example 10> Preparation of positive electrode active material The same procedure as in Example 7 was carried out, and the composition of the positive electrode active material for a lithium secondary battery that was subjected to the first heat treatment was Li 1.00 Ni 0.985 Al 0.014 Mg 0.001 O 2 Thus, a positive electrode active material of Example 10 was produced. The final composition formulas in the above-mentioned Examples 1 to 10 are summarized in the following . [Table 1]
[0043] <Comparative Example 2> The same procedure as in Example 4 was carried out, except that active material particles were added to a 0.1 mol cobalt aqueous solution, stirred, coated, and then dried to prepare a positive active material of Comparative Example 2.
[0044] <Comparative Example 3> A positive active material of Comparative Example 3 was prepared in the same manner as in Example 4, except that Co was not added during washing with water, and the Ti addition process and the second heat treatment were not performed.
[0045] <Experimental example> TEM, EDX measurement TEM and EDX images were taken of the surface of the secondary particles of the positive active material prepared in Comparative Example 2, and the results are shown in FIG. As shown in FIG. 15, in the case of the positive active material prepared in Comparative Example 2, Co is concentrated and distributed on the surface of the particles due to the process of adding active material particles to a cobalt aqueous solution and stirring them, but since a heat treatment process is not performed thereafter, the surface is not flat and Co is not doped into the inside.
[0046] <Comparative Example 4> The same procedure as in Comparative Example 3 was carried out, except that Ti was added at a concentration of 0.001 mol, and a second heat treatment was performed to prepare a positive active material of Comparative Example 4.
[0047] <Comparative Example 5> The positive electrode active material for a lithium secondary battery was prepared in the same manner as in Comparative Example 3, and the first heat treatment was performed. However, the water washing process was not performed after the preparation. Thus, a positive electrode active material of Comparative Example 5 was prepared.
[0048] <Comparative Example 6> The composition of the positive electrode active material for a lithium secondary battery that was subjected to the first heat treatment in the same manner as in Comparative Example 3 was Li 1.00 Ni 0.815 Co 0.15 Al 0.014 O 2 Thus, a positive electrode active material of Comparative Example 6 was produced.
[0049] <Comparative Example 7> The positive electrode active material for a lithium secondary battery was subjected to the same procedure as in Comparative Example 4 and the first heat treatment. Li 1.02 Ni 0.903 Co 0.08 Al 0.014 Mg 0.003 O 2 Thus, a positive electrode active material of Comparative Example 7 was produced.
[0050] <Comparative Example 8> The composition of the positive electrode active material for a lithium secondary battery that was subjected to the first heat treatment in the same manner as in Comparative Example 4 was Li 1.00 Ni 0.965 Co 0.02 Al 0.014 Mg 0.001 O2 Thus, a positive electrode active material of Comparative Example 8 was produced.
[0051] <Comparative Example 9> The same procedure as in Comparative Example 4 was carried out, and the first heat treatment was performed to prepare a positive electrode active material for a lithium secondary battery having a composition of Li1.00Ni0.985Al0.014Mg0.001O2, to prepare a positive electrode active material for Comparative Example 9. The final composition formulas in the first firing in the above-mentioned Comparative Examples 1 to 9 are summarized in the following . [Table 2]
[0052] <Experimental example> TEM, EDX measurement TEM and EDX images were taken of the surface of the secondary particles of the positive active material prepared in Comparative Example 4, and the results are shown in FIG. As can be seen from FIG. 16, in the case of the cathode active material prepared in Comparative Example 4, since the process of coating Co after the preparation of the active material was not performed, the Co concentration was uniformly distributed within the particles and no Co concentration gradient was observed from the surface to the inside of the particles.
[0053] <Experimental Example> Measurement of distance between crystal structures The diffraction pattern and interplanar distance were measured for the surface portions of the secondary particles of the positive active material prepared in Comparative Example 4, and the results are shown in FIG. As shown in FIG. 17, the diffraction pattern of the surface portion had a hexagonal structure, and the interplanar distance was measured to be 4.85 nm. The diffraction pattern and interplanar distance of the primary particles located inside the secondary particles of the positive active material prepared in Comparative Example 4 were measured, and the results are shown in FIG. As shown in FIG. 18, the diffraction pattern of the primary particles located inside the secondary particles of the positive active material is a hexagonal structure, and the interplanar distance is measured to be 4.83 nm. If Co coating is not performed, even after the second heat treatment, the primary particles located inside the secondary particles of the positive active material and the surface It can be seen that the interplanar distances of the positioned primary particles are almost similar.
[0054] <Experimental Example> Measurement of distance between crystal structures on the boundary surface of primary particles FIG. 19 shows the results of measuring the diffraction pattern and interplanar distance at the boundary surface of the primary particle located on the surface of the secondary particle of the positive active material prepared in Comparative Example 4. As shown in FIG. 19, the diffraction pattern at the boundary of the primary particles located on the surface of the secondary particles was a hexagonal structure, and the interplanar distances were measured to be 4.81 nm and 4.88 nm. In addition, in FIGS. 18 and 19, when no Co coating is performed, the diffraction patterns and interplanar distances inside and on the boundary surfaces of the primary particles are similar.
[0055] <Experimental Example> Concentration scanning The concentrations of Ni, Co, and Al were measured from the surface to the core of the secondary particles of the positive active material prepared in Comparative Example 4, and the results are shown in FIG. It can be seen from FIG. 20 that in the case of the positive active material prepared in Comparative Example 4 of the present invention, the concentrations of Ni, Co, and Al are constant within the particles.
[0056] <Experimental Example> Concentration scanning The concentrations of Ni, Co, and Al were measured in a direction parallel to the surface direction of the primary particles located on the surfaces of the secondary particles of the positive active material prepared in Comparative Example 4. The results are shown in FIG. As can be seen from FIG. 21, in the case of the cathode active material prepared in Comparative Example 4, the concentrations of Ni, Co, and Al are constant within the particles, the Co concentration does not show a gradient because no Co coating is performed, and the interplanar distance is similar between the surface and the interior.
[0057] <Experimental Example> XRD Measurement The LiCoO 2 The positive electrode active material was subjected to XRD measurement, and the results are shown in FIG. 22 and FIG. As shown in FIGS. 22 and 23, in the case of the positive electrode active material coated with Co and Ti prepared in Example 4 of the present invention, the LiCoO 2As shown in Fig. 1, the (104), (110), (113), (101), (102), and (003) peaks are detected.
[0058] <Experimental Example> XRD Measurement The positive electrode active material of Comparative Example 2 was subjected to XRD measurement, and the results are shown in FIG. As shown in FIG. 24, in the case of the positive electrode active material produced in Comparative Example 2 of the present invention, only a peak due to Co(OH)2 was detected, and no peak due to LiCoO 2 It can be seen that the peaks (104), (110), (113), (101), (102), and (003) which are characteristically detected in
[0059] <Experimental Example> XRD Measurement XRD measurements were performed on the positive active materials of Comparative Example 4, which was not Co-coated, and Example 4, which was Co-coated and then heat-treated. The results are shown in FIG. As shown in FIG. 25, in the case of the positive electrode active material of Comparative Example 4 in which the Co coating of the present invention is not performed, LiCoO 2 It can be seen that the peaks (104), (110), (113), (101), (102), and (003) which are characteristically detected in
[0060] <Experimental Example> XPS Measurement XPS was measured for the positive electrode active materials of Comparative Example 4, which was not coated with Co, and Example 3, which was coated with a cobalt aqueous solution having a concentration of 5 mol %, and the results are shown in FIG. As shown in FIG. 26, when cobalt coating is performed during the water washing process according to the present invention, It can be seen that the intensity of the Co 2p peak is larger than that of Comparative Example 4, and that such a peak is mostly due to Co+3. 2 CO 3 It can be seen that the intensity of the peak due to
[0061] <Experimental Example> Residual Lithium Measurement The residual lithium in the composite oxides prepared in Examples 1 to 10 and Comparative Examples 4 to 9 was measured, and the results are shown in Table 3 below. In order to measure the residual lithium, 1 g of the active material was immersed in 5 g of distilled water and stirred for 5 minutes, and the filtrate was dissolved in 0.1 M HCl. The volume of HCl added until the pH of the filtrate reached 5 was measured to analyze the residual lithium of the active material. As can be seen from Table 3 below, in the case of the active material prepared according to the embodiment of the present invention, the amount of residual lithium is significantly reduced compared to the case of Comparative Example 5 where the calcination process is not performed. [Table 3]
[0062] <Manufacturing example> Battery manufacturing The positive electrode active materials prepared in Examples 1 to 10 and Comparative Examples 4, 6 to 9 were mixed with Super-P as a conductive agent and polyvinylidene fluoride (PVdF) as a binder in a weight ratio of 92:5:3 to prepare a slurry. The slurry was uniformly coated on an aluminum foil having a thickness of 15 μm and dried in a vacuum at 135° C. to prepare a positive electrode for a lithium secondary battery. The positive electrode and a lithium wheel were used as counter electrodes, a porous polyethylene film (Celgard 2300, manufactured by Celgard LLC, thickness: 25 μm) was used as a separator, and LiPF was dissolved in a solvent containing ethylene carbonate and ethyl methyl carbonate in a volume ratio of 3:7. 6 is 1.15M concentration A coin battery was manufactured by a commonly known manufacturing process using a liquid electrolyte dissolved in water.
[0063] <Experimental Example> Battery characteristic measurement - Initial capacity The initial capacities of the batteries manufactured using the active materials manufactured in Examples 1 to 10 and Comparative Examples 4, 6 to 9 were measured, and the results are shown in FIG. 27a (Examples 1 to 4, Comparative Example 4), FIG. 27b (Example 5, Comparative Example 6), FIG. 27c (Example 6, Comparative Example 7), FIG. 27d (Examples 7 to 9, Comparative Example 8), and FIG. 27e (Example 10, Comparative Example 9). 27a to 27e, when Co coating was performed according to the embodiment of the present invention, the capacity and efficiency characteristics were measured to be superior to those of the comparative example. The initial capacity measurement results of the batteries manufactured using the active materials manufactured in Examples 1 to 10 and Comparative Examples 4, 6 to 9 are summarized in Table 4 below. [Table 4]
[0064] <Experimental Example> Battery characteristic measurement - Efficiency characteristics The efficiency characteristics of the batteries manufactured using the active materials manufactured in Examples 1 to 10 and Comparative Examples 4, 6 to 9 were measured, and the results are shown in Figure 28a (Examples 1 to 4, Comparative Example 4), Figure 28b (Example 5, Comparative Example 6), Figure 28c (Example 6, Comparative Example 7), Figure 28d (Examples 7 to 9, Comparative Example 8), and Figure 28e (Example 10, Comparative Example 9). 28a to 28e, it was measured that the capacity and efficiency characteristics of the Co-coated battery according to the embodiment of the present invention were superior to those of the comparative example. The efficiency characteristics of the batteries manufactured using the active materials manufactured in Examples 1 to 10 and Comparative Examples 4, 6 to 9 are shown in Table 5 below. [Table 5]
[0065] <Experimental Example> Battery characteristic measurement - Life characteristics The life characteristics of the batteries manufactured using the active materials manufactured in Examples 1 to 10 and Comparative Examples 4, 6 to 9 were measured, and the results are shown in Figure 29a (Examples 1 to 4, Comparative Example 4), Figure 29b (Example 5, Comparative Example 6), Figure 29c (Example 6, Comparative Example 7), Figure 29d (Examples 7 to 9, Comparative Example 8), and Figure 29e (Example 10, Comparative Example 9). 28a to 28e, it can be seen that when Co coating is performed according to the embodiment of the present invention, the life characteristics are improved compared to the comparative example. The results of measuring the life characteristics of the batteries manufactured using the active materials manufactured in Examples 1 to 10 and Comparative Examples 4, 6 to 9 are summarized in Table 6 below. [Table 6]
[0066] <Experimental Example> Battery characteristic measurement - High temperature storage characteristics The high temperature storage characteristics of the batteries manufactured using the active materials manufactured in Examples 1 to 3, 5 to 10 and Comparative Examples 4, 6 to 9 were measured, and the results before storage are shown in Figure 30a (Examples 1 to 3, Comparative Example 4), Figure 30b (Example 5, Comparative Example 6), Figure 30c (Example 6, Comparative Example 7), Figure 30d (Examples 7 to 9, Comparative Example 8), and Figure 30e (Example 10, Comparative Example 9), and the results after storage are shown in Figure 31a (Examples 1 to 3, Comparative Example 4), Figure 31b (Example 5, Comparative Example 6), Figure 31c (Example 6, Comparative Example 7), Figure 31d (Examples 7 to 9, Comparative Example 8), and Figure 31e (Example 10, Comparative Example 9). Referring to Figures 30a to 30e and Figures 31a to 31e, it can be seen that when Co coating is performed according to an embodiment of the present invention, the impedance does not increase significantly after high temperature storage compared to the comparative example, and therefore the high temperature storage characteristics are significantly improved. The results of measuring high temperature storage characteristics of the batteries manufactured using the active materials manufactured in Examples 1 to 3, 5 to 10 and Comparative Examples 4, 6 to 9 are summarized in below. [Table 7]
Claims
1. A lithium composite oxide secondary particle formed by agglomeration of a plurality of primary particles, the interplanar distance of the crystal structure in the primary particle decreases from the center toward the surface of the secondary particle, The secondary particles include a Co coating layer on the surface thereof, the thickness of the Co coating layer on the surface is 80 nm to 140 nm; The secondary particles include lithium, nickel and cobalt, The lithium composite oxide secondary particles have a hexagonal structure, The secondary particles have at least one peak at (104), (110), (113), (101), (102), and (003) positions in XRD analysis; The secondary particles are represented by the following <Chemical Formula 1>: 【Chemistry 1】 (In the <Chemical Formula 1>, M1 is Al, M2 is Co, M3 is selected from the group consisting of Al, Ba, B, Co, Ce, Cr, F, Li, Mg, Mn, Mo, P, Sr, Ti, and Zr, and 0.95≦X1≦1.05, 1.50≦a≦2.1, 0.02≦x1≦0.25, 0.01≦y1≦0.20, 0<z1≦0.20, 0≦r1≦0.20)
2. The lithium composite oxide secondary particle according to claim 1 , wherein the interplanar distance d1 of the crystal structure of the primary particle at the center of the secondary particle is 4.8 nm or more.
3. The lithium composite oxide secondary particle according to claim 1 , wherein the interplanar distance d2 of the crystal structure of the primary particle on the surface of the secondary particle is 4.7 nm or less.
4. The secondary particles of the lithium composite oxide according to claim 1, wherein the binding energy (P1) of the spin-orbit-spit 2p3 / 2 peak and the binding energy (P2) of the 2p1 / 2 peak are in the ranges as follows, in a Co 2p core-level spectrum analysis obtained through an XPS measurement. 779eV≦(P1)≦780eV 794eV≦(P2)≦795eV
5. 2. The lithium composite oxide secondary particles according to claim 1, wherein the ratio of a peak intensity (I531) near 531 eV to a peak intensity (I528) near 528.5 eV in an O 1s core-level spectrum analysis obtained through an XPS measurement is as follows: (I531) / (I528)≦2
6. 2. The lithium composite oxide secondary particles according to claim 1, wherein the ratio of a peak intensity (I289) near 289 eV to a peak intensity (I284) near 284.5 eV in a C 1s core-level spectrum analysis obtained through an XPS measurement is as follows: (I289) / (I284)≦0.9
7. 2. A method for producing secondary particles of a lithium composite oxide according to claim 1, comprising the steps of: A first step of producing a positive electrode active material precursor for a lithium secondary battery; a second step of reacting the positive electrode active material precursor for a lithium secondary battery with a lithium compound and carrying out a first heat treatment to prepare a positive electrode active material; a third step of washing the positive electrode active material with distilled water or an alkaline aqueous solution; A fourth step of coating the washed positive electrode active material with a solution containing one or more selected from Al, Ba, B, Co, Ce, Cr, F, Li, Mg, Mn, Mo, P, Sr, Ti, and Zr; a fifth step of drying the positive electrode active material particles; a sixth step of mixing the dried positive electrode active material with Co and performing a second heat treatment to dope Co into the inside of the particles; Inclusive of The secondary particles are represented by the following <Chemical Formula 1>. 【Chemistry 2】 (In the <Chemical Formula 1>, M1 is Al, M2 is Co, M3 is selected from the group consisting of Al, Ba, B, Co, Ce, Cr, F, Li, Mg, Mn, Mo, P, Sr, Ti, and Zr, and 0.95≦X1≦1.05, 1.50≦a≦2.1, 0.02≦x1≦0.25, 0.01≦y1≦0.20, 0<z1≦0.20, 0≦r1≦0.20)
8. A lithium secondary battery comprising the lithium composite oxide secondary particles according to claim 1.
9. 9. The lithium secondary battery according to claim 8, wherein the residual lithium in the lithium secondary battery is 6000 ppm or less.
Citation Information
Patent Citations
Positive electrode active material, nonaqueous electrolyte battery and manufacturing method of positive electrode active material
JP2012018827A
Polycrystalline metal oxide, method for producing the same, and product containing the same
JP2014528891A
Cathod active material for lithium rechargeable battery and lithium rechargeable battery comprising the same
KR101555594B1
Process for the production of lithium-manganese double oxide for lithium ion batteries and lithium-manganese double oxide for lithium ion batteries made by ...
KR1020110108566A
Method for manufacturing cathode active material for lithium secondary battery and cathode active material for lithium secondary battery manufactured thereby
KR1020140081663A